2018
DOI: 10.1007/s10886-018-0962-0
|View full text |Cite
|
Sign up to set email alerts
|

Birds Bug on Indirect Plant Defenses to Locate Insect Prey

Abstract: It has long been thought that most birds do not use volatile cues to perceive their environment. Aside from some scavenging birds, this large group of vertebrates was believed to mostly rely on highly developed vision while foraging and there are relatively few studies exploring bird response to volatile organic compounds. In response to insect herbivory, plants release volatile organic compounds to attract parasitoids and predators of the pests. To test if insectivorous birds use herbivore-induced plant volat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 11 publications
1
23
1
Order By: Relevance
“…Furthermore, artificial larvae near dispensers with the aggregation pheromone had proportionally more bird pecks than larvae near the control dispenser. These results support previous findings showing that insectivorous birds can use chemical cues to locate and consume their prey 8,9,11,25,27,49,50]. Considering that many birds prey on immature stages of insects, the capacity to perceive chemical cues emitted by insect larvae would be of great ecological relevance in birds' foraging strategies.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, artificial larvae near dispensers with the aggregation pheromone had proportionally more bird pecks than larvae near the control dispenser. These results support previous findings showing that insectivorous birds can use chemical cues to locate and consume their prey 8,9,11,25,27,49,50]. Considering that many birds prey on immature stages of insects, the capacity to perceive chemical cues emitted by insect larvae would be of great ecological relevance in birds' foraging strategies.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, woodpeckers (Picidae) were shown to regulate the population of bark beetles (Curculionidae) in coniferous forest landscapes [67]. Moreover, different studies have demonstrated that insectivorous birds use herbivore-induced plant volatiles as olfactory cues to locate their prey in agricultural ecosystems [25,49]. Within this context, the capacity of birds to detect insect-derived chemical cues, such as sexual or aggregation pheromones, may present an opportunity for the regulation of insect populations in human-modified landscapes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though olfaction previously has been dismissed as being unimportant for most bird species, it has turned out to play an important role in bird foraging behavior (Mäntylä et al, 2004;Hiltpold and Shriver, 2018;Potier, 2020;Danel et al, 2021). Some bird species can use their sense of smell to identify caterpillarinfested trees by detection of herbivore induced plant volatiles (HIPVs) (Mäntylä et al, 2004(Mäntylä et al, , 2020Amo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Herbivorous larvae may also be the most important part of the diet for many bird species, especially while provisioning their young, which suggests that HIPVs could be important for foraging efficiency. Indeed, several studies have demonstrated bird attraction to or preference for HIPVs both in the laboratory (Amo et al, 2013;Mäntylä et al, 2017) and in the field (Mrazova and Sam, 2017;Hiltpold and Shriver, 2018;Rubene et al, 2019).…”
Section: Introductionmentioning
confidence: 99%